A Conversation with Lynn Meskell - Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2021)
Lynn Meskell is PIK Professor of Anthropology in the School of Arts and Sciences, Professor in the Graduate Program in Historic Preservation, and curator in the Middle East and Asia sections at the Penn Museum. She is currently A.D. White Professor-at-Large at Cornell University (2019–2025). She holds Honorary Professorships at Oxford University and Liverpool University in the UK and the University of the Witwatersrand, South Africa. Over the past twenty years she has been awarded grants and fellowships including those from the Andrew W. Mellon Foundation, the National Science Foundation, the Australian Research Council, the American Academy in Rome, the School of American Research, Oxford University and Cambridge University. She is the founding editor of the Journal of Social Archaeology. Meskell has broad theoretical interests including socio-politics, archaeological ethics, global heritage, materiality, as well as feminist and postcolonial theory. Her earlier research examined natural and cultural heritage in South Africa, the archaeology of figurines and burial in Neolithic Turkey and daily life in New Kingdom Egypt.